1991
DOI: 10.1111/j.1365-2621.1991.tb04769.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Composition and Some Antinutritional Factors of Cooked Faba Beans (Medammis): Effects of Cooking Temperature and Time

Abstract: Easy-and hard-to-cook bean seeds were cooked by different heat treatments (lOO-12S'C for 1-12 hr). Amino acid composition, tannins, phytic acid and trypsin inhibitor activity were determined. Almost all essential amino acids declined after cooking. Less than 10% of total tannins were decomposed during cooking, while up to 50% were leached to the cooking liquor. Retention of phytic acid in cooked beans was significantly lower than in cooked bean-liquor mixtures. Loss of phytic acid due to leaching was much high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…It has been claimed that decomposition of some protein fractions rich in essential amino acids resulted in higher values for non-essential amino acids when they were calculated on the basis of 100% protein. 20 It is difficult to compare the results cited above with those obtained in the present experiment, since not all of these papers concerned pulse crops at the stage of milk maturity,15h17 none concerning the broad bean.…”
Section: Resultsmentioning
confidence: 79%
“…It has been claimed that decomposition of some protein fractions rich in essential amino acids resulted in higher values for non-essential amino acids when they were calculated on the basis of 100% protein. 20 It is difficult to compare the results cited above with those obtained in the present experiment, since not all of these papers concerned pulse crops at the stage of milk maturity,15h17 none concerning the broad bean.…”
Section: Resultsmentioning
confidence: 79%
“…According to Youssef et al [18], long-lasting thermal treatment reduces exogenous amino acids to drastic degree. Ziena et al [4] applying a constant period of thermal treatment, observed an increase, a constant level, or a decrease in the level of different amino acids in broad bean seeds. In spite of increases or decreases in the content of different amino acids, Khalil and Mansour [3] did not observe any effects of heat on the total amount of exogenous amino acids.…”
Section: Amino Acid Contentmentioning
confidence: 98%
“…In the international literature most studies on the broad bean concerned seeds of physiological maturity or various kinds of dishes and products obtained from seeds in this stage of maturity [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Lisiewska et al stated that a food product is a complex matrix, with peptides, polypeptides and free amino acids [18]; therefore, it is difficult to determine the reason for changes in individual amino acids. However, the decomposition of certain protein fractions rich in amino acids can bring about increases in the content of other amino acids [19].…”
Section: Amino Acid Contentsmentioning
confidence: 99%